The Effect of Using Aqueous Extract of Cyperus Rotundus Tubers on Characteristics and Shelf Life of Chicken Nuggets - AM Ali, Hala; SR Zangana, Bushra; H Abdullah, Ikram (The Iraqi Journal of Veterinary Medicine, 2024)
The experiment was conducted to investigate the effect of the aqueous extract of the Cyperus ‎rotundus tubers ‎on fat oxidation and stored frozen chicken nuggets’ physical and microbial ‎characteristics. The extract was incorporated into minced poultry meat at concentrations of 0% (control), 0.1%, 0.2%, 0.3%, and 0.4%, and the treated samples were stored for periods of 1 and 30 days at -18°C. The addition of Cyperus rotundus extract significantly improved the pH values and water-holding capacity of the treated nuggets (T2, T3, T4, and T5) compared to the control (T1) across both storage durations. Moreover, a notable reduction in lipid oxidation markers (peroxide value (PV), thiobarbituric acid reactive substances (TBA), free fatty acids (FFA), and total volatile nitrogen (TVN) was observed in the treated samples relative to the control. Additionally, a significant decrease in the total coliform bacteria count was evident in the treated nuggets, which inversely correlated with the concentration of the Cyperus rotundus extract. The findings suggest that the aqueous extract of Cyperus rotundus tubers beneficially affects the quality and safety of chicken nuggets, enhancing their shelf life when stored at -18°C for up to 30 days‎‎‎.